MOTIF KETERLIBATAN MAHASISWA KATOLIK PERANTAU DI KOTA MALANG DALAM LEGIO MARIA - Gregorius Pasi; Videlis Gon (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2025)
A number of Catholic students from other cities in Malang are the members of the Legion of Mary. This phenomenon is relevant to be studied because the presence of the Legion of Mary in the Catholic Church and the involvement of young people in it is very important. The Legion of Mary is a lay apostolic group. The presence of lay apostles is very important. However, the composition of the Legion of Mary members is dominated by older people. Not many young people become legionaries. There is an impression that the Legion of Mary is not suitable for them. In order to eliminate this impression and in order to formulate the right way to promote the Legion of Mary among the young people, it is necessary to examine their motives to become legionaries. For this purpose, we examine the motives of involvement of a number of Catholic students in Presidium Maria Bunda Perjalanan. The status quaestionis of this study is: what are the motives of the involvement of Catholic students in the Legion of Mary? The method used in this study is qualitative with a phenomenological approach. Data from research subjects were collected using observation techniques and direct interviews. We found that the involvement of the subjects in the Legion of Mary was motivated by three main motives, namely spiritual, social, and self-development motives. Therefore, in order to promote the Legion of Mary among the students, these three motives need to be presented.